Analysis of Differences in Volatile Components of Five Lauraceae Plants From Different Genera Based on HS-SPME-GC-MS - Zhengjiu Wang; Hao Liu; Anping Liu; Peng Liu; Jiuyang Zhao; Shaoli Fan; Jinhui Wang; Bahetiyar Keremu; Lu Yang; Le Li (Journal of Analytical Methods in Chemistry)
Lauraceae plants are diverse in species and rich in volatile components, which possess functions such as insect repellency, antioxidant activity, and antibacterial properties. However, currently, the methods for analyzing the volatile components of Lauraceae plants are relatively single. The essential oils are mainly extracted by steam distillation, but the pretreatment is relatively complex and cumbersome. Therefore, it is essential to find a simple and cost-effective method. By comparing different extraction methods, HS-SPME-GC-MS was selected as the optimal extraction condition. Regarding Head-space Solid-Phase Microextraction and Gas Chromatography-Mass Spectrometry (HS-SPME-GC-MS), single-factor condition optimization and response surface analysis were carried out for different fiber coatings, equilibrium time, extraction temperature, and extraction time. Eventually, 75-μm CAR/PDMS fiber head was chosen, with an equilibrium time of 15 min, and extraction was conducted at 70°C for 57 min as the optimal HS-SPME extraction conditions. Furthermore, a differential analysis of the volatile components of five Lauraceae plants from different genera was performed, and differential metabolites were screened out respectively. This can effectively separate Cinnamomum and Litsea from the other three genera, providing certain assistance for the chemotaxonomy of the volatile components of Lauraceae plants and the subsequent development of medicinal plant resources.